Do Consulting Services Affect Audit Quality? Evidence from the Workforce - Fedyk, Anastassia; Fedyk, Tatiana; Hodson, James; Khimich, Natalya (The Accounting Review, 2026)
ABSTRACT This paper investigates how consulting services affect audit quality, from the perspective of knowledge- and expertise-sharing between employees. Semistructured interviews with 16 audit partners reveal that consulting expertise is used in 60–80 percent of audit engagements, with the main rationale for such collaboration being knowledge-sharing and improved audit quality. We leverage a comprehensive office-level dataset of employment profiles covering 86 percent of all employees at large U.S. public accounting firms to systematically investigate the effect of consulting employees on audit quality. We document that a one standard deviation increase in the share of consulting employees in an office results in a 2.6 percentage point reduction in restatements (a decrease of 19 percent relative to the baseline). This effect is strongest when consulting employees have skills complimentary to auditors, e.g., technical and human resources skills, and when consultants have specific industry expertise in the same industry as the audit client. Data Availability: Data from common sources, such as Audit Analytics, can be purchased from the providers. Data on firm-level measures of workforce characteristics and skills are available from the authors upon request, conditional on approval from the data provider (Cognism). JEL Classifications: D22; E24; J24; M42.